El derecho a la verdad en el ámbito iberoamericano - Luis Giancarlo Torreblanca Gonzales (Universidad Hemisferios, 2012)
This paper persued to establish the origin of the Right to the Truth in Latin America, after this, it describes the statements issued by the American Court of Human Rights on this important right and its reception by the principles contained in the American Convention on Human Rights and as the scope that comes giving; this work concludes with a brief discussion of the reception they have had the judgments of the Inter-American Court of Human Rights in the Latinamerican Courts.